2021
DOI: 10.1097/nna.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Impact of Schwartz Center Rounds on Moral Distress

Abstract: Moral distress occurs when moral integrity is compromised and can affect any healthcare professional. This study examined the impact of Schwartz Center Rounds (SCRs) on moral distress using a longitudinal, quasi-experimental design to examine SCR attendees from 2015 to 2019. Data were collected via a 2-part survey composed of demographics and Moral Distress Thermometer (MDT) readings before rounds and immediately after rounds. Most participants experienced either no change in moral distress (50.6%) or a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This is a consistently arranged meeting where nurses can share and discuss social and emotional issues that are encountered during the care of their patients and families (Schwartz, 1995). This approach has been used to nurture functioning teams while promoting wellness and reducing the experience of moral distress among nurses (Whitehead et al, 2021). Maben et al (2021) concluded that the programme provide staff with a deep thoughtful and confidential environment where nurses speak and acknowledge the part they play in the care of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is a consistently arranged meeting where nurses can share and discuss social and emotional issues that are encountered during the care of their patients and families (Schwartz, 1995). This approach has been used to nurture functioning teams while promoting wellness and reducing the experience of moral distress among nurses (Whitehead et al, 2021). Maben et al (2021) concluded that the programme provide staff with a deep thoughtful and confidential environment where nurses speak and acknowledge the part they play in the care of patients.…”
Section: Discussionmentioning
confidence: 99%